Sexual Functioning and Behavior of Men with Body Dysmorphic Disorder Concerning Penis Size Compared with Men Anxious about Penis Size and with Controls: A Cohort Study. Issue 3 (1st September 2015) - Veale, David; Miles, Sarah; Read, Julie; Troglia, Andrea; Wylie, Kevan; Muir, Gordon
Abstract: Introduction: Little is known about the sexual functioning and behavior of men anxious about the size of their penis and the means that they might use to try to alter the size of their penis. Aim: To compare sexual functioning and behavior in men with body dysmorphic disorder (BDD) concerning penis size and in men with small penis anxiety (SPA without BDD) and in a control group of men who do not have any concerns. Methods: An opportunistic sample of 90 men from the community were recruited and divided into three groups: BDD (n = 26); SPA (n = 31) and controls (n = 33). Main Outcome Measures: The Index of Erectile Function (IEF), sexual identity and history; and interventions to alter the size of their penis. Results: Men with BDD compared with controls had reduced erectile dysfunction, orgasmic function, intercourse satisfaction and overall satisfaction on the IEF. Men with SPA compared with controls had reduced intercourse satisfaction. There were no differences in sexual desire, the frequency of intercourse or masturbation across any of the three groups. Men with BDD and SPA were more likely than the controls to attempt to alter the shape or size of their penis (for example jelqing, vacuum pumps or stretching devices) with poor reported success. Conclusion: Men with BDD are more likely to have erectile dysfunction and less satisfaction with intercourse than controls but maintain their libido. Further research is required to develop and evaluate a psychological intervention for such men with adequate outcome measures.